Apatites: Crystal Size, Morphology, and Growth Mechanism in Bio‐Inspired Apatite Nanocrystals (Adv. Funct. Mater. 8/2014). (February 2014) - Delgado‐López, José Manuel; Frison, Ruggero; Cervellino, Antonio; Gómez‐Morales, Jaime; Guagliardi, Antonietta; Masciocchi, Norberto
<x xml:space="preserve">Abstract</x> Nanocrystalline apatite platelets, the mineral component of bone, form from an amorphous precursor through a complex biomineralization process. Here, A. Guagliardi and co‐workers use citrate‐bio‐inspired apatites as a system model and, by cross‐coupling the results on crystal domains provided by X‐ray total scattering modeling with atomic force microscopy observations, they reconstruct the amorphousto‐crystal transformation mechanism and clarify the origin of the platy morphology breaking the hexagonal crystal symmetry. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>